Social security and safety of older adults in Poland - Urbaniak, Bogusława (Magyar Gerontológia, 2020)
Poland’ population will be ageing at a fast rate in the coming decades. It is projected that in 2070 the Polish ratio between people aged 65 and over and those aged 15-64 years will be 62.6, the highest among EU-27 countries. Population ageing appeared in the public debate in Poland as a separate subject in the 1990s, following a negative natural population increase and the looming impact of the massive withdrawal of baby boomers from the labour market on the pension system. One of the reasons for older persons’ growing interest in retirement was pension system reforms planned by successive governments. The announcement of the year 2012 as the European Year for Active Ageing and Solidarity Between Generations (decision no. 940/2011/EU of the European Parliament and of the Council of 14 September 2011) contributed in Poland to the emergence of a senior policy from a social policy and initiated major legislative, institutional, and organisational changes at the national, regional and local levels of government. It also inspired the redefinition of measures used hitherto in line with the evolution in the perception of older people from social care recipients to active members of their communities entitled to education and economic, social, civic and political activity. In 2013, the Senior Policy Council was established as a consultative and advisory body to the Ministry of Labour and Social Policy, and then similar councils supporting regional and local authorities were organised. In order to encourage greater activity among seniors, a special governmental programme was created in December 2013, which grants funds on a competitive basis to projects concerning social activities, education, and intergenerational cooperation submitted by informal and formal groups of seniors. The national government’s key documents on senior policy, one for the period from 2014 to 2020 and the other spanning the years until 2030, are Resolution 238 of 24 Dec. 2013 by the Board of Ministers on the Adoption of Long-term Senior Policy in Poland for the Years 2015-2020 and Resolution 161 of 28 Oct. 2018 by the Board of Ministers on the adoption of Social Policy Towards the Older Persons 2030. Security-Participation-Solidarity. In 2015, the Polish Parliament passed the elderly people act, which requires institutions in charge of the well-being of older persons to monitor and report on their situation. The reports submitted by the institutions are used by the Ministry of Labour to compile and present an annual evaluation of the status of the older population in Poland. The regional governments’ senior policy is reflected in their social policy strategies. The strategies’ operational goals started to address needs specific to older people since 2002, focusing in particular on improving their quality of life, developing round-the-clock care services, at-home care services, and rehabilitation services, and on reducing social exclusion and marginalization of seniors. Social security and the safety of older adults are progressively improving in Poland, but the greatest progress has been made in the area of active ageing. Social care services for the elderly still require improvement, because the predominant family care model is inefficient in many ways due to: • limited financing of care services by public institutions, • the growing proportion of single elderly persons, • the increasing number of people aged 85+ (the so-called double population ageing), • social insurance disregarding long-term care to an elderly family member as an insurable risk, • a lack of legislation allowing employed people to seek a long-term leave to give care to an older family member, • the informal expectation that women who retire at the age of 60 years will take care of the oldest family members. While neither the scale nor the quality of home care services given to older persons is regularly surveyed in Poland, it can be presumed that the scale of care services is insufficient and that they excessively burden families with a member in need of care. Between 2010 and 2018, the number of persons aged 65+ increased in Poland by over 1.5 million, the number of the users of attendance services and specialised attendance services by 29,000 (from 99,000 to 128,000), and the number of residences in homes and facilities providing assistance to aged persons by 7,000 (from 20,000 to 27,100.)